Size-dependent aggregation of erythrocytes by low molecular weight hyaluronic acids of different sizes: bioactivity and quality control potential - Ma, Xinyue; Wang, Xiao; Jia, XiaoXiao; Hui, Jessica H.; Shofaro, Joshua H.; Tao, Ran; Hui, Mizhou Matthew (Frontiers in Physiology, 2025)
IntroductionHyaluronic acid (HA) is a crucial biological molecule whose diverse functions are strongly influenced by its molecular weight. In particular, low molecular weight HA (LMW-HA) fragments—such as HA60 (average 60 kDa), HA35 (average 35 kDa), and HA24 (average 24 kDa)—exhibit enhanced tissue permeability and unique interactions with cell surfaces compared to high molecular weight HA (HMW-HA). This study investigates the size-dependent aggregation effects of LMW-HA on erythrocytes and examines the implications for bioactivity, quality control, and therapeutic applications.MethodsWe investigated the effects of LMW-HA fragments on erythrocyte aggregation across molecular sizes using erythrocyte sedimentation rate (ESR) assays, CD44 receptor blocking assays, and molecular weight assessment via gel electrophoresis and GPC-MALLS. LMW-HA samples were applied at varying concentrations to measure their binding affinity to erythrocytes, while CD44 antibodies were used to assess receptor involvement. Species-specificity of aggregation was examined by comparing erythrocytes from different animals.ResultsLMW-HA induced erythrocyte aggregation in a size-dependent manner, with HA60 exhibiting the strongest binding affinity, followed by HA35 and HA24. Aggregation was partially reversible and could be inhibited by CD44 antibodies, indicating a receptor-mediated interaction. Minimum effective concentrations for aggregation were inversely related to molecular weight, with lower molecular weight fragments requiring higher concentrations. Species-specific effects were also observed, highlighting variations in erythrocyte-HA interactions across different animals.DiscussionThe study suggests that LMW-HA facilitates erythrocyte aggregation through CD44-mediated binding, offering insights into HA’s role in erythrocyte physiology and its effects on blood rheology. The findings support the potential of LMW-HA for therapeutic applications in pain and inflammation management, given its enhanced tissue permeability and reversible interaction with erythrocytes. Additionally, the size-dependent aggregation provides a valuable parameter for quality control, enabling consistency in LMW-HA products. These results underscore the importance of molecular weight in determining HA’s physiological and pharmacological activity, paving the way for further clinical research to confirm species-specific effects and optimize safe therapeutic uses of LMW-HA.